2019
DOI: 10.3390/medicina55070379
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Exercise Intervention on Psychological and Physical Fitness in Lymphoma Patients

Abstract: Background and objectives: Lymphoma patients experience a psychological and physiological decline that could be reversed by exercise. However, little is known about the effects of the exercise on psychological and physical fitness variables. Therefore, the purpose of this longitudinal study was to assess self-efficacy, fatigue and physical fitness before and after an eight-week exercise intervention. Materials and Methods: Thirty-six participants (54.4 ± 19.1 years) performed a supervised exercise program (~60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 47 publications
0
27
0
2
Order By: Relevance
“…However, randomized studies have shown the substantial improvement in QoL of cancer patients due to an adequate program of physical activity [23][24][25]34] and impact the cancer survival [7], since it reduces the peak oxygen consumption, improves physical capacity, increases self-esteem, reduces accumulated stress, and promotes relaxation [8,11]. Consequently, physical activity is strongly recommended for healthy individuals to improve cardiorespiratory and muscular fitness, bone health, and in general to reduce the risk of non-communicable diseases, depression, and cognitive decline [11] The correct application of an exercise program may have a beneficial effect in onco-hematologic patients, since it may improve the function of the immune system (regulation of macrophages and natural killer cells interacting with cancer cells) [9,10] and provide a protective effect against cancer progression. In our clinical center, we encourage cancer patients, to progressively increase their physical activity, depending on their abilities and attitudes, according to the Cancer Patient Support Organizations such as the Lymphoma Action and includes walks, planned exercises, sports activities, domestic activities, and professional activities [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, randomized studies have shown the substantial improvement in QoL of cancer patients due to an adequate program of physical activity [23][24][25]34] and impact the cancer survival [7], since it reduces the peak oxygen consumption, improves physical capacity, increases self-esteem, reduces accumulated stress, and promotes relaxation [8,11]. Consequently, physical activity is strongly recommended for healthy individuals to improve cardiorespiratory and muscular fitness, bone health, and in general to reduce the risk of non-communicable diseases, depression, and cognitive decline [11] The correct application of an exercise program may have a beneficial effect in onco-hematologic patients, since it may improve the function of the immune system (regulation of macrophages and natural killer cells interacting with cancer cells) [9,10] and provide a protective effect against cancer progression. In our clinical center, we encourage cancer patients, to progressively increase their physical activity, depending on their abilities and attitudes, according to the Cancer Patient Support Organizations such as the Lymphoma Action and includes walks, planned exercises, sports activities, domestic activities, and professional activities [26].…”
Section: Discussionmentioning
confidence: 99%
“…In these clinical cases, active and passive motor rehabilitation is necessary to maintain a muscle tone to favor an upright position and, whenever possible, walking capacity [7,8]. Subsequently, patients should be helped and then more in small steps or remained in an upright position with prolonged support [9,10]. The 2017 guidelines of the Italian Association of Medical Oncology (AIOM) recommend physical activity in neoplastic cachexia.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors have been identified in research as contributing to fatigue, but it is still unclear what is most influent (Ryan et al, 2007). Physiological and psychosocial factors play a part in the specific mechanisms involved in the development of CRF (Ahlberg et al, 2003;Fischetti et al, 2019); an import contribute was made by muscular metabolism (Brown et al, 2005;Forsyth et al, 1999;Isaksson et al, 2002;Lane et al, 1998;Lee et al, 2003;McCully et al, 1996). For assessment and management of CRF, different scales and questionnaire were made (Cleeland et al, 1999;Mendoza et al, 1999;Piper, 1997;Piper et al, 1989;Piper et al, 1998;Schwartz, 1998;Schwart & Meek, 1999;Smets et al, 1995;Sutherland et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Training can produce extremely important effects, as older people use a considerable proportion of their functional capacity to perform even simple everyday activities [39]. Programs include aerobic exercise to increase muscle endurance, exercises to strengthen the extensor muscles of the legs (which support the ability to walk and get up from a chair), and the upper limbs, useful for carrying out household chores and other activities of daily life [40].…”
Section: Introductionmentioning
confidence: 99%